The affordability of the middle income group to own a house case study : Pengkalan Chepa, Kota Bharu Kelantan / Noorazmira Mohd Afandi - Mohd Afandi, Noorazmira (2010)
This study aims to investigate the problem of owning a residential by the middle income class. The main focus is on the middle class or middle-income group. This category is selected as the government policy only emphasizes the low income class by providing guidance only for the low income earner, but without realizing it, this action has resulted difficulties for the middle income earner. Among the objectives of this study is to identify the level of income, background and ability of the middle class to own a home. In addition, this study is to examine the problems faced by this group of home ownership. When problems are identified, the propose Solution is actions by the government to provides such a pricing policy for medium-cost houses and only middle income earners are eligible to buy. To identify this problem, I have been doing some research, namely through questionnaires and interviews. Among the feedbacks obtained from the middle class is that the house price are too expensive and even though them are eligible to buy it through bank bans, they still have problems in terms of paying the monthly payment. Therefore, governments and financial institutions need to provide residential owning process with moderate cost with hire purchase concept is gradual based and the rental fee charged every month is in line with the income earned.